2017
DOI: 10.1016/j.ajhg.2017.02.003
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamic Role of trans Regulation of Gene Expression in Relation to Complex Traits

Abstract: Identifying causal genetic variants and understanding their mechanisms of effect on traits remains a challenge in genome-wide association studies (GWASs). In particular, how genetic variants (i.e., trans-eQTLs) affect expression of remote genes (i.e., trans-eGenes) remains unknown. We hypothesized that some trans-eQTLs regulate expression of distant genes by altering the expression of nearby genes (cis-eGenes). Using published GWAS datasets with 39,165 single-nucleotide polymorphisms (SNPs) associated with 1,9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(99 citation statements)
references
References 50 publications
6
93
0
Order By: Relevance
“…Based on the PhenoScanner database, we found that rs10830963 appeared to affect the expression levels of distant genes. Emerging evidence suggests that some SNPs affect the expression of distant genes and genes residing on other chromosomes (trans‐eQTLs) . Thus, it is biologically plausible that rs10830963 may affect the expression of genes and be involved in the pathogenesis of GDM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the PhenoScanner database, we found that rs10830963 appeared to affect the expression levels of distant genes. Emerging evidence suggests that some SNPs affect the expression of distant genes and genes residing on other chromosomes (trans‐eQTLs) . Thus, it is biologically plausible that rs10830963 may affect the expression of genes and be involved in the pathogenesis of GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that some SNPs affect the expression of distant genes and genes residing on other chromosomes (trans-eQTLs). 30,31 Thus, it is biologically plausible that rs10830963 may affect the expression of genes and be involved in the pathogenesis of GDM. However, functional studies are needed to confirm this.…”
Section: Discussionmentioning
confidence: 99%
“…A general rule is that the more distant the eQTLs, the more cell‐ and context‐specific and the lower their effect sizes. These distant eQTLs may be cis‐ eQTLs of a transcription factor (TF) that in turn controls distant targets . Besides, a given trans‐ eQTL may control several genes and thus operate as a master regulator like in the Major Histocompatibility Complex (MHC) …”
Section: Genome‐wide Genetic Studies Of Expression Phenotypesmentioning
confidence: 99%
“…These distant eQTLs may be cis-eQTLs of a transcription factor (TF) that in turn controls distant targets. 91 Besides, a given trans- ⋍ 0…”
Section: Demographic and Evolutionary Forcesmentioning
confidence: 99%
See 1 more Smart Citation